Membangun Karakter Bangsa dengan Nilai-nilai Keutamaan dalam Bhagavad Gita Suatu Kajian Pustaka atas Karya Ngakan Putu Putra - Diana Dewi Andayani (UHN IGB Sugriwa Denpasar, 2016)
Lately, characters become very serious conversation. Various Portals of Government Agencies which are associated with education makes the characters as the project theme of national seminars. In a variety of social media will very often be found articles related to the characters. This is because the Indonesian Government is anxious to see the reality of nation’s community mental which is experiencing a crisis and moral degradation. Cases of corruption and human tragedy that were done by those who are supposedly literate even become a spectacle on various TV stations. It encourages the government of Indonesia sought to reformulate the National Education Goals as outlined in UUSPN No. 20 of 2003 Article 3. That article states that education aims to develop students' potential to become a human of faith and piety to God Almighty, noble, healthy, knowledgeable, skilled, creative, independent, and become democratic and accountable citizens to the community and nationality. All are then formulated into 18 (eighteen) grains of the noble values of the nation then called the values of the character as a means to build the nation's character. Although the Indonesian government has formulated 18 characters to build the nation's character, but various groups, community leaders and academics are still eager to participate to complement the Government's thoughts. This article shall discuss a book by national Hindu leaders, namely Ngakan Putu Putra, a comprehensive work explored in the literature that explores the Bhagavadgita which discusses 27 (twenty-seven) character value that gives hope for the realization of the nation's character.